Low-melting-point flame-retardant polyester sheath-core fiber as well as preparation method and application thereof
By introducing zero-dimensional nanoparticles and phosphorus-containing flame-retardant chain segments into the cortex of the low melting point flame-retardant polyester leather core fibers, and introducing modified two-dimensional nanosheets into the core layer, the problems of low flame retardant efficiency and poor mechanical performance in the prior art are solved, and more efficient flame retardant and mechanical performance improvement are achieved.
Patent Information
- Application Number
- CN202311281941.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The existing low-melting point flame retardant polyester leather core fibers have low flame retardant efficiency, relatively poor mechanical properties, and fail to effectively regulate the interface bonding ability between the cortex and the core layer.
Zero-dimensional nanoparticles and two phosphorus-containing flame retardant chain segments are introduced into the cortex to improve the melt viscosity and strength of the polyester; modified two-dimensional nanosheets are introduced as interface enhancers in the core layer, and interface binding ability is enhanced through the regulation of the components of the skin core layer and the surface microstructure.
The flame retardant efficiency and mechanical properties of the low-melting point flame retardant polyester leather core fiber are significantly improved, and the flame retardant effect of the condensed phase and the anti-droplet performance are enhanced.
Smart Images

Figure BDA0004478615380000051 
Figure BDA0004478615380000061 
Figure BDA0004478615380000201
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fibers, and in particular relates to a low-melting-point flame-retardant polyester sheath-core fiber and a preparation method and application thereof. Background Art
[0002] Low-melting-point polyester fiber with a core-skin structure is a new type of fiber material; the core layer is conventional polyester and the skin layer is low-melting-point polyester. Due to the presence of low-melting-point polyester in the skin layer, the low-melting-point polyester core-skin fiber has the advantages of low-temperature bonding, strong bonding, non-toxicity, and no pollution. It is considered a "green adhesive" and is widely used in the automotive industry, rail transit, architectural decoration, medical and health, home textiles and other fields. However, polyester fiber is a flammable material with certain safety hazards, and flame retardant properties have become a technical bottleneck restricting its safe use.
[0003] There have been relevant reports on the preparation of low-melting flame-retardant polyester sheath-core fibers. Among them, Korean patent KR20070059064 discloses a low-melting flame-retardant polyester sheath-core fiber that improves flame retardancy by introducing a third monomer through copolymerization. Specifically, the copolymerization method is used to introduce hypophosphorous acid derivatives into the polyester molecular chain to improve the flame retardancy of the core polyester, but the skin layer is not flame-retardantly treated, and finally a low-melting flame-retardant polyester fiber with a skin-core structure having a melting point of 110-190°C for the skin layer and a melting point of 220-260°C for the core layer is obtained. Korean patent KR20160039738 discloses a low-melting flame-retardant polyester sheath-core fiber in which the skin layer and the core layer are simultaneously copolymerized and flame-retardantly modified. The melting point of the skin layer is 110-158°C, the melting point of the core layer is 230-280°C, the oxygen index can reach 36%, and it obtains UL94 V1 grade and has no droplets.
[0004] Patent CN201710018844.2 discloses a low-melting flame-retardant polyester sheath-core fiber with a flame-retardant core layer using 2-carboxyethylphenylphosphite as the third monomer. However, the sheath is not flame-retardantly treated, and the prepared sheath-core structure low-melting flame-retardant polyester fiber has a melting point of 100-170°C and an oxygen index greater than 28%. Although there is a method for preparing a low-melting flame-retardant polyester sheath-core fiber, there are still the following limitations: (1) Under the existing technical conditions, the flame retardant efficiency of the flame-retardant fiber obtained by spinning after copolymerization is not high when 2-carboxyethylphosphite derivatives are simply used as flame-retardant comonomers; (2) Under the existing technical conditions, the interface bonding ability between the sheath and the core layer is not regulated, and the mechanical properties are relatively poor; (3) Under the existing technical conditions, the flame retardant and additives are not compounded, and the synergistic flame retardant cannot be achieved. Therefore, it is an urgent problem to provide a polyester sheath-core fiber with high flame retardant efficiency and good mechanical properties. Summary of the invention
[0005] The main purpose of the present invention is to provide a low melting point flame retardant polyester sheath core fiber and its preparation method and application, so as to overcome the problems of low melting point flame retardant polyester sheath core fiber in the prior art, such as low flame retardant efficiency and relatively poor mechanical properties.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0007] The embodiment of the present invention provides a low melting point flame retardant polyester sheath-core fiber, which comprises a sheath layer and a core layer;
[0008] The cortex comprises a low-melting polyester and zero-dimensional nanoparticles dispersed in the low-melting polyester, the molecular structure of the low-melting polyester comprises a polyester segment and a phosphorus-containing flame-retardant segment, and the phosphorus-containing flame-retardant segment is derived from 2-carboxyethylphenylphosphite and [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid;
[0009] The core layer includes conventional melting point polyester, phosphorus-containing non-reactive flame retardant dispersed in the conventional melting point polyester and modified two-dimensional nanosheets, wherein the phosphorus-containing non-reactive flame retardant includes any one or more combinations of phosphate flame retardants and phosphaphenanthrene flame retardants.
[0010] The embodiment of the present invention also provides a method for preparing the aforementioned low melting point flame retardant polyester sheath-core fiber, which comprises:
[0011] The low melting point polyester monomer, phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are mixed and copolymerized, and then enter the extruder through a pipeline, extruded and granulated to obtain a skin polyester material;
[0012] The conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets are mixed and melted, extruded and granulated to obtain a core layer polyester material;
[0013] Furthermore, the sheath layer polyester material and the core layer polyester material are subjected to melt spinning to obtain low melting point flame retardant polyester sheath-core fiber.
[0014] The embodiments of the present invention also provide the use of the aforementioned low melting point flame retardant polyester sheath-core fiber in the automotive industry, rail transportation, architectural decoration, medical and health care or home textile fields.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] (1) The present invention introduces zero-dimensional nanoparticles into the sheath of the low-melting flame-retardant polyester sheath-core fiber to adjust the melt viscosity and melt strength of the polyester, give it good anti-melting droplet performance, and enhance the condensed phase flame retardant effect; two phosphorus-containing flame retardant segments (2-carboxyethylphenyl hypophosphite and [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid) are introduced into the low-melting flame-retardant polyester to play a synergistic flame retardant role;
[0017] (2) The present invention introduces a modified two-dimensional nanosheet with a high aspect ratio as an interface enhancer into the core layer of the low-melting point flame-retardant polyester sheath-core fiber, wherein the modified two-dimensional nanosheet is surface-modified with melamine amide, which, on the one hand, increases the interlayer spacing, making it easier to evenly disperse into the polyester matrix, thereby ensuring good spinnability; on the other hand, the lamellar nanostructure can migrate to the surface during combustion, thereby playing a better barrier role, thereby blocking the heat and combustible gas exchange between the outer carbon layer and the inner resin layer, thereby playing a role in enhancing flame retardancy;
[0018] (3) The present invention regulates the core-skin layer components and surface microstructures, and the polarity of the skin copolymer flame retardant is greater than that of the polyester itself, which is beneficial to interfacial bonding. The modified two-dimensional nanosheets in the core layer are radially oriented during the spinning process, and part of them exist at the skin-core interface, increasing the interface roughness and enhancing the interface bonding ability synergistically. The core layer flame retardant mainly acts in the gas phase, while the skin layer flame retardant mainly acts in the condensed phase. The two synergistically can enhance the flame retardant efficiency of the skin-core structure. DETAILED DESCRIPTION
[0019] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Specifically, as one aspect of the technical solution of the present invention, a low melting point flame retardant polyester sheath-core fiber includes a sheath layer and a core layer;
[0021] The cortex comprises a low-melting polyester and zero-dimensional nanoparticles dispersed in the low-melting polyester, the molecular structure of the low-melting polyester comprises a polyester segment and a phosphorus-containing flame-retardant segment, and the phosphorus-containing flame-retardant segment is derived from 2-carboxyethylphenylphosphite and [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid;
[0022] The core layer includes conventional melting point polyester, phosphorus-containing non-reactive flame retardant dispersed in the conventional melting point polyester and modified two-dimensional nanosheets, wherein the phosphorus-containing non-reactive flame retardant includes any one or more combinations of phosphate flame retardants and phosphaphenanthrene flame retardants.
[0023] In some preferred embodiments, the low melting point polyester has a melting point lower than the melting point of the conventional melting point polyester.
[0024] In some preferred embodiments, the skin layer includes the following components calculated by weight: 100 parts of low melting point polyester and 0.1 to 3 parts of zero-dimensional nanoparticles.
[0025] In some preferred embodiments, the mass ratio of the low melting point polyester to the zero-dimensional nanoparticles in the skin layer is 100:(0.5-2).
[0026] Furthermore, the mass ratio of the low melting point polyester to the zero-dimensional nanoparticles in the skin layer is 100:(1-1.5).
[0027] In some preferred embodiments, the skin layer accounts for 10 to 50 wt % of the total mass of the low melting point flame retardant polyester sheath-core fiber.
[0028] In some preferred embodiments, the intrinsic viscosity of the low melting point polyester is 0.54 to 0.68 dL / g.
[0029] Furthermore, the intrinsic viscosity of the low melting point polyester is 0.58 to 0.66 dL / g.
[0030] Furthermore, the intrinsic viscosity of the low melting point polyester is 0.60-0.64 dL / g.
[0031] In some preferred embodiments, the low melting point polyester has a melting point of 85°C to 145°C.
[0032] In some preferred embodiments, the polyester segment includes a terephthalic acid segment, an isophthalic acid segment, an ethylene glycol segment, and a diethylene glycol segment.
[0033] Furthermore, the molar ratio of the terephthalic acid segment, the isophthalic acid segment, the ethylene glycol segment and the diethylene glycol segment is 1:(0.2-0.5):(1.8-2.5):(0.2-0.4).
[0034] In some preferred embodiments, the mass ratio of the low melting point polyester to the phosphorus-containing flame retardant segment in the low melting point polyester is 100:(3-10).
[0035] Furthermore, the mass ratio of the low melting point polyester to the phosphorus-containing flame retardant segment in the low melting point polyester is 100:(5-7).
[0036] In some preferred embodiments, the zero-dimensional nanoparticles include any one or more combinations of nano-silicon dioxide and nano-carbon black, but are not limited thereto.
[0037] In some preferred embodiments, the core layer includes the following components calculated in parts by weight: 100 parts of conventional melting point polyester, 8-20 parts of phosphorus-containing non-reactive flame retardant and 0.1-3 parts of modified two-dimensional nanosheets.
[0038] In some preferred embodiments, the mass ratio of the conventional melting point polyester to the phosphorus-containing non-reactive flame retardant in the core layer is 100:(10-18).
[0039] Furthermore, the mass ratio of the conventional melting point polyester to the phosphorus-containing non-reactive flame retardant in the core layer is 100:(13-16).
[0040] In some preferred embodiments, the mass ratio of the conventional melting point polyester to the modified two-dimensional nanosheets in the core layer is 100:(0.5-2).
[0041] Furthermore, the mass ratio of the conventional melting point polyester to the modified two-dimensional nanosheets in the core layer is 100:(1-1.5).
[0042] In some preferred embodiments, the molecular structure of the conventional melting point polyester includes a terephthalic acid segment and an ethylene glycol segment.
[0043] In some preferred embodiments, the normal melting point polyester includes polyethylene terephthalate (PET), but is not limited thereto.
[0044] In some preferred embodiments, the conventional melting point polyester has a melting point of 235°C to 265°C.
[0045] In some preferred embodiments, the conventional melting point polyester has an intrinsic viscosity of 0.65 to 0.85 dL / g.
[0046] Furthermore, the intrinsic viscosity of the conventional melting point polyester is 0.68 to 0.80 dL / g.
[0047] Furthermore, the intrinsic viscosity of the conventional melting point polyester is 0.70 to 0.75 dL / g.
[0048] In some preferred embodiments, the phosphate flame retardant includes a compound having a structure represented by formula (I) or formula (II):
[0049]
[0050] In some preferred embodiments, the phosphaphenanthrene flame retardant includes a compound having a structure shown in formula (III):
[0051]
[0052] In some preferred embodiments, the phosphorus-containing flame retardant segment is (2-carboxyethylphenylphosphite), ([(6-Oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid) (DDP) is formed after copolymerization.
[0053] In some preferred embodiments, the modified two-dimensional nanosheets are obtained by surface-modifying the two-dimensional nanosheets with melamine amide.
[0054] Furthermore, the two-dimensional nanosheets include any one or more combinations of nano-sized montmorillonite, attapulgite, illite, and sepiolite, but are not limited thereto.
[0055] In some preferred embodiments, the preparation method of the modified two-dimensional nanosheets includes: replacing calcium ions in the two-dimensional nanosheets with sodium ions, then blending the two-dimensional nanosheets with sodium ions with melamine amide, and further adding phosphoric acid for ultrasonic stirring reaction to obtain surface functionalized high aspect ratio two-dimensional nanosheets, namely: modified two-dimensional nanosheets.
[0056] In some more specific embodiments, the method for preparing the modified two-dimensional nanosheet comprises:
[0057] Step 1: Disperse the two-dimensional nanosheets in a saturated solution of sodium chloride to allow sufficient ion exchange, so that the sodium ions can replace the calcium ions from between the sheets to obtain two-dimensional nanosheets whose interlayer exchangeable cations are sodium ions; the replacement temperature is 25 to 85°C, and the replacement time is 1 to 24 hours;
[0058] Step 2: Re-disperse the two-dimensional nanosheets (cations are sodium ions) obtained by replacement in deionized water, add melamine amide, stir at high speed, and mix thoroughly; the stirring temperature is 65-85° C., and the replacement time is 1-6 hours;
[0059] Step 3: adding excess phosphoric acid to the mixed solution prepared in step 2, stirring at constant temperature and ultrasonically, and reacting for several hours; wherein the molar ratio of the two-dimensional nanosheet (the cation is sodium ion), melamine amide and phosphoric acid is 1: (0.1-0.3): (0.2-1.0), the reaction temperature is 30-90° C., and the reaction time is 1-12 hours;
[0060] Step 4: let the reaction solution stand for a certain period of time, remove the supernatant to obtain the precipitate, repeatedly wash it with deionized water, and filter it under reduced pressure to obtain a high aspect ratio two-dimensional nanosheet with a modified melamine amide surface, that is, a modified two-dimensional nanosheet; the standing time is 8 to 16 hours.
[0061] In some preferred embodiments, the aspect ratio of the modified two-dimensional nanosheet is 5-16.
[0062] In some preferred embodiments, the material of the conventional melting point polyester in the core layer of the present invention includes, for example, polyethylene terephthalate (PET). The "non-reactive" in the phosphorus-containing non-reactive flame retardant means that the flame retardant will not react with the core layer polyester matrix. The phosphate flame retardant includes (denoted as: non-reactive flame retardant 1), (denoted as: non-reactive flame retardant 2); the phosphaphenanthrene flame retardant is (Note: non-reactive flame retardant 3); these three phosphorus-containing non-reactive flame retardants have high flame retardant efficiency and good compatibility with the core layer polyester matrix.
[0063] In some preferred embodiments, the low-melting flame-retardant polyester sheath-core fiber has a tensile strength of 3.7 to 5.4 cN / dtex, an elongation at break of 12% to 23%, and a limiting oxygen index of 34 to 46%.
[0064] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned low melting point flame retardant polyester sheath-core fiber, which comprises:
[0065] The low melting point polyester monomer, phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are mixed and copolymerized, and then enter the extruder through a pipeline, extruded and granulated to obtain a skin polyester material;
[0066] The conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets are mixed and melted, extruded and granulated to obtain a core layer polyester material;
[0067] Furthermore, the sheath layer polyester material and the core layer polyester material are subjected to melt spinning to obtain low melting point flame retardant polyester sheath-core fiber.
[0068] In some preferred embodiments, the low melting point polyester monomer includes terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol and a phosphorus-containing flame retardant monomer, wherein the phosphorus-containing flame retardant monomer includes 2-carboxyethylphenylphosphite and [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid (DDP).
[0069] Furthermore, the molar ratio of 2-carboxyethylphenylphosphorous acid to [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid in the phosphorus-containing flame retardant monomer is (2-8):(8-2).
[0070] Furthermore, the molar ratio of 2-carboxyethylphenylphosphorous acid to [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid in the phosphorus-containing flame retardant monomer is (4-6):(6-4).
[0071] In some preferred embodiments, the process conditions adopted in the melt spinning process include: spinning temperature of 285°C to 330°C, spinning speed of 3000m / min to 4200m / min; stretching temperature of 65°C to 80°C, and stretching multiple of 2.4 to 3.2 times.
[0072] Furthermore, the spinning temperature is 300° C. to 315° C., the spinning speed is 3800 m / min to 4000 m / min; the drawing temperature is 70° C. to 75° C., and the drawing multiple is 2.7 to 2.9 times.
[0073] In some preferred embodiments, the preparation method further comprises: drying the raw materials before melt spinning.
[0074] In some preferred embodiments, the preparation method further comprises:
[0075] The two-dimensional nanosheet is subjected to ion replacement treatment to obtain a two-dimensional nanosheet having sodium ions;
[0076] And, the two-dimensional nanosheets having sodium ions are mixed with melamine amide and stirred fully, and then phosphoric acid is added and ultrasonically stirred to react to obtain the modified two-dimensional nanosheets.
[0077] In some more specific embodiments, the method for preparing the modified two-dimensional nanosheet comprises:
[0078] Step 1: Disperse the two-dimensional nanosheets in a saturated solution of sodium chloride to allow sufficient ion exchange, so that the sodium ions can replace the calcium ions from between the sheets to obtain two-dimensional nanosheets whose interlayer exchangeable cations are sodium ions; the replacement temperature is 25 to 85°C, and the replacement time is 1 to 24 hours;
[0079] Step 2: Re-disperse the two-dimensional nanosheets (cations are sodium ions) obtained by replacement in deionized water, add melamine amide, stir at high speed, and mix thoroughly; the stirring temperature is 65-85° C., and the replacement time is 1-6 hours;
[0080] Step 3: adding excess phosphoric acid to the mixed solution prepared in step 2, stirring at constant temperature and ultrasonically, and reacting for several hours; wherein the molar ratio of the two-dimensional nanosheet (the cation is sodium ion), melamine amide and phosphoric acid is 1: (0.1-0.3): (0.2-1.0), the reaction temperature is 30-90° C., and the reaction time is 1-12 hours;
[0081] Step 4: let the reaction solution stand for a certain period of time, remove the supernatant to obtain the precipitate, repeatedly wash it with deionized water, and filter it under reduced pressure to obtain a high aspect ratio two-dimensional nanosheet with a modified melamine amide surface, that is, a modified two-dimensional nanosheet; the standing time is 8 to 16 hours.
[0082] As a particularly preferred embodiment of the present application, the method for preparing the low-melting point flame-retardant polyester sheath-core fiber comprises:
[0083] (1) Copolymerizing a low-melting polyester monomer, a phosphorus-containing flame-retardant chain segment and zero-dimensional nanoparticles at 235°C to 245°C, and extruding and granulating to obtain a skin layer low-melting polyester material (i.e., the aforementioned "skin layer polyester material") having a melting point of 105°C to 125°C; the mass ratio of the low-melting polyester monomer, the phosphorus-containing flame-retardant chain segment and the zero-dimensional nanoparticles is 100:(5-7):(1-1.5).
[0084] (2) conventional melting point polyester, phosphorus-containing non-reactive flame retardant and high aspect ratio two-dimensional nanosheets (the aforementioned "modified two-dimensional nanosheets") are mixed, melt blended at 275°C to 280°C, and extruded into granules to obtain a core layer polyester material (i.e., the aforementioned "core layer polyester material") having a melting point of 245°C to 255°C; the mass ratio of conventional melting point polyester, phosphorus-containing non-reactive flame retardant and high aspect ratio two-dimensional nanosheets is 100:(13-16):(1-1.5);
[0085] The characteristic viscosity of the core layer polyester matrix is 0.70-0.75 dL / g; the phosphorus-containing non-reactive flame retardant is selected from non-reactive flame retardant 1, non-reactive flame retardant 2 or non-reactive flame retardant 3; and the high aspect ratio two-dimensional nanosheets are selected from modified two-dimensional montmorillonite, attapulgite, illite or sepiolite.
[0086] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and melt spinning is performed to obtain a low-melting point flame-retardant polyester core-skin fiber, wherein the skin layer accounts for 25 to 35 wt% of the total mass of the low-melting point flame-retardant polyester core-skin fiber; wherein the spinning temperature is 300°C to 315°C, the spinning speed is 3800 m / min to 4000 m / min; the drawing temperature is 70°C to 75°C, and the drawing multiple is 2.7 to 2.9 times.
[0087] Another aspect of the embodiments of the present invention further provides the use of the aforementioned low melting point flame retardant polyester sheath-core fiber in the automotive industry, rail transportation, architectural decoration, medical and health care or home textile fields.
[0088] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments. This embodiment is implemented on the premise of the technical solution of the invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0089] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0090] The preparation method of the two-dimensional nanosheets surface-modified with melamine amide in the following examples includes:
[0091] Step 1: Disperse the two-dimensional nanosheets (nano-montmorillonite, attapulgite, illite or sepiolite) in a saturated solution of sodium chloride to allow sufficient ion exchange. Sodium ions can replace calcium ions from between the sheets to obtain two-dimensional nanosheets whose interlayer exchangeable cations are sodium ions; the replacement temperature is 55°C and the replacement time is 12h;
[0092] Step 2: Re-disperse the two-dimensional nanosheets (cations are sodium ions) obtained by replacement in deionized water, add melamine amide, stir at high speed, and mix thoroughly; the stirring temperature is 74° C., and the replacement time is 3 h;
[0093] Step 3: adding excess phosphoric acid to the mixed solution prepared in step 2, stirring at constant temperature and ultrasonically, and reacting for several hours; wherein the molar ratio of the two-dimensional nanosheet (cation is sodium ion), melamine amide and phosphoric acid is 1:0.2:0.6, the reaction temperature is 64°C, and the reaction time is 7.2h;
[0094] Step 4: Allow the reaction solution to stand for a certain period of time, remove the supernatant to obtain a precipitate, repeatedly wash with deionized water, and filter under reduced pressure to obtain a high aspect ratio two-dimensional nanosheet with a modified melamine amide surface, i.e., a modified two-dimensional nanosheet (including modified montmorillonite, modified attapulgite, modified illite or modified sepiolite); the standing time is 12 hours.
[0095] Example 1
[0096] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0097] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, a phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 240° C., extruded and granulated to obtain a low-melting-point polyester material for the skin layer, the melting point of which is 115° C.; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, the phosphorus-containing reactive flame retardant and the zero-dimensional nanoparticles is 100:6:1.25;
[0098] The molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.35:2.15:0.3; the phosphorus-containing reactive flame retardant is 2-carboxyethylphenyl hypophosphorous acid and DDP, and the molar ratio of the two is 5:5; the zero-dimensional nanoparticles are nano-silicon dioxide.
[0099] (2) mixing a conventional melting point polyester, a phosphorus-containing non-reactive flame retardant and a modified two-dimensional nanosheet, melt blending at 277° C., and extruding and granulating to obtain a core layer polyester material having a melting point of 250° C.; the mass ratio of the conventional melting point polyester, the phosphorus-containing non-reactive flame retardant and the modified two-dimensional nanosheet is 100:15:1.25;
[0100] Among them, the characteristic viscosity of conventional melting point polyester is 0.72 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 1; and the modified two-dimensional nanosheet is modified montmorillonite.
[0101] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 30wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 307°C, the spinning speed is 3900m / min; the drawing temperature is 72°C, and the drawing multiple is 2.8 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0102] Example 2
[0103] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0104] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 245°C and extruded into granules to obtain a low-melting point polyester material having a skin layer and a melting point of 125°C; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles is 100:5:1.0;
[0105] The molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.3:2.1:0.25; the phosphorus-containing reactive flame retardant is 2-carboxyethylphenyl hypophosphorous acid and DDP, and the molar ratio of the two is 5:5; the zero-dimensional nanoparticles are nano carbon black.
[0106] (2) mixing a conventional melting point polyester, a phosphorus-containing non-reactive flame retardant and a modified two-dimensional nanosheet, melt blending at 275° C., and extruding and granulating to obtain a core layer polyester material having a melting point of 245° C.; the mass ratio of the conventional melting point polyester, the phosphorus-containing non-reactive flame retardant and the modified two-dimensional nanosheet is 100:13:1.0;
[0107] Among them, the characteristic viscosity of conventional melting point polyester is 0.70 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 2; and the modified two-dimensional nanosheet is modified attapulgite.
[0108] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 25wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 315°C, the spinning speed is 4000m / min; the drawing temperature is 70°C, and the drawing multiple is 2.7 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0109] Example 3
[0110] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0111] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, a phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 235° C., extruded and granulated to obtain a low-melting-point polyester material for the skin layer, with a melting point of 105° C.; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, the phosphorus-containing reactive flame retardant and the zero-dimensional nanoparticles is 100:7:1.5;
[0112] The molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.4:2.2:0.35; the phosphorus-containing flame retardant segment uses 2-carboxyethylphenylphosphite and DDP, and the molar ratio of the two is 5:5; the zero-dimensional nanoparticles use nano-silicon dioxide.
[0113] (2) mixing a conventional melting point polyester, a phosphorus-containing non-reactive flame retardant and a modified two-dimensional nanosheet, melt blending at 280° C., and extruding and granulating to obtain a core layer polyester material having a melting point of 255° C.; the mass ratio of the conventional melting point polyester, the phosphorus-containing non-reactive flame retardant and the modified two-dimensional nanosheet is 100:16:1.5;
[0114] The characteristic viscosity of the conventional melting point polyester of the core layer is 0.75 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 3; and the modified two-dimensional nanosheet is modified illite.
[0115] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 35wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 300°C, the spinning speed is 3800m / min; the drawing temperature is 75°C, and the drawing multiple is 2.9 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0116] Example 4
[0117] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0118] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, a phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 252° C., extruded and granulated to obtain a low-melting-point polyester material for the skin layer, with a melting point of 135° C.; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, the phosphorus-containing reactive flame retardant and the zero-dimensional nanoparticles is 100:5:1.0;
[0119] The molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.25:2.0:0.27; the phosphorus-containing flame retardant segment uses 2-carboxyethylphenylphosphite and DDP, and the molar ratio of the two is 4:6; the zero-dimensional nanoparticles use nano-silicon dioxide.
[0120] (2) mixing a conventional melting point polyester, a phosphorus-containing non-reactive flame retardant and a modified two-dimensional nanosheet, melt blending at 270° C., and extruding and granulating to obtain a core layer polyester material having a melting point of 240° C.; the mass ratio of the conventional melting point polyester, the phosphorus-containing non-reactive flame retardant and the modified two-dimensional nanosheet is 100:13:1.0;
[0121] The characteristic viscosity of the conventional melting point polyester of the core layer is 0.68 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 1; and the modified two-dimensional nanosheet is modified sepiolite.
[0122] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 20wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 322°C, the spinning speed is 4100m / min; the drawing temperature is 67°C, and the drawing multiple is 2.5 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0123] Example 5
[0124] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0125] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, a phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 227° C., extruded and granulated to obtain a low-melting-point polyester material having a skin layer and a melting point of 95° C.; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, the phosphorus-containing reactive flame retardant and the zero-dimensional nanoparticles is 100:7:1.5;
[0126] Among them, the molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.45:2.3:0.32; the phosphorus-containing flame retardant segment uses 2-carboxyethylphenyl hypophosphorous acid and DDP, and the molar ratio of the two is 6:4; the zero-dimensional nanoparticles use nano-silicon dioxide and nano-carbon black.
[0127] (2) mixing a conventional melting point polyester, a phosphorus-containing non-reactive flame retardant and a modified two-dimensional nanosheet, melt blending at 285° C., and extruding and granulating to obtain a core layer polyester material having a melting point of 260° C.; the mass ratio of the conventional melting point polyester, the phosphorus-containing non-reactive flame retardant and the modified two-dimensional nanosheet is 100:16:1.5;
[0128] The characteristic viscosity of the conventional melting point polyester of the core layer is 0.8 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 1; and the modified two-dimensional nanosheet is modified montmorillonite.
[0129] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 40wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 292°C, the spinning speed is 3400m / min; the drafting temperature is 77°C, and the drafting multiple is 3.0 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0130] Example 6
[0131] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0132] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, a phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 250° C., extruded and granulated to obtain a low-melting-point polyester material for the skin layer, the melting point of which is 130° C.; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, the phosphorus-containing reactive flame retardant and the zero-dimensional nanoparticles is 100:4.5:0.7;
[0133] The molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.27:2.0:0.28; the phosphorus-containing flame retardant segment uses 2-carboxyethylphenyl hypophosphorous acid and DDP, and the molar ratio of the two is 5:5; the zero-dimensional nanoparticles use nano-silicon dioxide or nano-carbon black.
[0134] (2) mixing a conventional melting point polyester, a phosphorus-containing non-reactive flame retardant and a modified two-dimensional nanosheet, melt blending at 272° C., and extruding and granulating to obtain a core layer polyester material having a melting point of 243° C.; the mass ratio of the conventional melting point polyester, the phosphorus-containing non-reactive flame retardant and the modified two-dimensional nanosheet is 100:12:0.8;
[0135] The characteristic viscosity of the conventional melting point polyester of the core layer is 0.69 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 2; and the modified two-dimensional nanosheet is modified attapulgite.
[0136] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 22wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 320°C, the spinning speed is 4150m / min; the drawing temperature is 68°C, and the drawing multiple is 2.6 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0137] Example 7
[0138] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0139] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, a phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 230° C., extruded and granulated to obtain a low-melting-point polyester material for the skin layer, the melting point of which is 110° C.; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, the phosphorus-containing reactive flame retardant and the zero-dimensional nanoparticles is 100:7.5:1.7;
[0140] The molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.42:2.25:0.34; the 2-carboxyethylphenyl hypophosphorous acid phosphorus-containing flame retardant segment is 2-carboxyethylphenyl hypophosphorous acid and DDP, and the molar ratio of the two is 5:5; the zero-dimensional nanoparticles are nano-silicon dioxide or nano-carbon black.
[0141] (2) mixing conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets, melt blending and extrusion granulation at 282° C. to obtain a core layer polyester material with a melting point of 256° C.; the mass ratio of conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets is 100:17:1.8;
[0142] The characteristic viscosity of the conventional melting point polyester of the core layer is 0.77 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 2; and the modified two-dimensional nanosheet is modified attapulgite.
[0143] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 38wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 295°C, the spinning speed is 3600m / min; the drawing temperature is 76°C, and the drawing multiple is 2.95 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0144] Example 8
[0145] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0146] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, a phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 260° C., extruded and granulated to obtain a low-melting-point polyester material for the skin layer, with a melting point of 145° C.; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, the phosphorus-containing reactive flame retardant and the zero-dimensional nanoparticles is 100:3:0.1;
[0147] The molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.2:1.8:0.2; the phosphorus-containing flame retardant segment is 2-carboxyethylphenylphosphite and DDP, and the molar ratio of the two is 5:5; the zero-dimensional nanoparticles are nano-silicon dioxide or nano-carbon black.
[0148] (2) mixing conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets, melt blending and extrusion granulation at 265° C. to obtain a core layer polyester material with a melting point of 235° C.; the mass ratio of conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets is 100:8:0.1;
[0149] The characteristic viscosity of the conventional melting point polyester of the core layer is 0.65 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 3; and the modified two-dimensional nanosheet is a mixture of modified attapulgite and modified montmorillonite.
[0150] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 10wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 330°C, the spinning speed is 4200m / min; the drawing temperature is 65°C, and the drawing multiple is 2.4 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0151] Example 9
[0152] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0153] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, a phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 220° C., extruded and granulated to obtain a low-melting-point polyester material for the skin layer, with a melting point of 85° C.; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, the phosphorus-containing reactive flame retardant and the zero-dimensional nanoparticles is 100:10:3;
[0154] The molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.5:2.5:0.4; the phosphorus-containing flame retardant segment uses 2-carboxyethylphenyl hypophosphorous acid and DDP, and the molar ratio of the two is 4:6; the zero-dimensional nanoparticles use nano-silicon dioxide or nano-carbon black.
[0155] (2) mixing a conventional melting point polyester, a phosphorus-containing non-reactive flame retardant and a modified two-dimensional nanosheet, melt blending at 290° C., and extruding and granulating to obtain a core layer polyester material having a melting point of 265° C.; the mass ratio of the conventional melting point polyester, the phosphorus-containing non-reactive flame retardant and the modified two-dimensional nanosheet is 100:20:3.0;
[0156] The characteristic viscosity of the conventional melting point polyester of the core layer is 0.85 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 3; and the modified two-dimensional nanosheet is modified attapulgite.
[0157] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 50wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 285°C, the spinning speed is 3000m / min; the drawing temperature is 80°C, and the drawing multiple is 3.2 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0158] Example 10
[0159] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0160] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, a phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 256° C., extruded and granulated to obtain a low-melting-point polyester material for the skin layer, the melting point of which is 140° C.; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, the phosphorus-containing reactive flame retardant and the zero-dimensional nanoparticles is 100:3.5:0.3;
[0161] The molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.22:1.9:0.22; the phosphorus-containing flame retardant segment uses 2-carboxyethylphenyl hypophosphorous acid and DDP, and the molar ratio of the two is 6:4; the zero-dimensional nanoparticles use nano-silicon dioxide or nano-carbon black.
[0162] (2) mixing conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets, melt blending and extrusion granulation at 267° C. to obtain a core layer polyester material with a melting point of 236° C.; the mass ratio of conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets is 100:9:0.3;
[0163] The characteristic viscosity of the conventional melting point polyester of the core layer is 0.66 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 1; and the modified two-dimensional nanosheet is modified sepiolite.
[0164] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 15wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 325°C, the spinning speed is 4150m / min; the drawing temperature is 66°C, and the drawing multiple is 2.45 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0165] Embodiment 11
[0166] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0167] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, a phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 224° C., extruded and granulated to obtain a low-melting-point polyester material for the skin layer, with a melting point of 90° C.; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, the phosphorus-containing reactive flame retardant and the zero-dimensional nanoparticles is 100:9:2.5;
[0168] The molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.46:2.4:0.36; the phosphorus-containing flame retardant segment uses 2-carboxyethylphenyl hypophosphorous acid and DDP, and the molar ratio of the two is 7:3; the zero-dimensional nanoparticles use nano-silicon dioxide.
[0169] (2) mixing conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets, melt blending and extrusion granulation at 284° C. to obtain a core layer polyester material with a melting point of 257° C.; the mass ratio of conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets is 100:19:2.5;
[0170] The characteristic viscosity of the conventional melting point polyester of the core layer is 0.83 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 2; and the modified two-dimensional nanosheet is modified attapulgite.
[0171] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 12wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 290°C, the spinning speed is 3300m / min; the drawing temperature is 78°C, and the drawing multiple is 3.1 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0172] Example 12
[0173] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0174] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, a phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 259° C., extruded and granulated to obtain a low-melting-point polyester material for the skin layer, with a melting point of 143° C.; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, the phosphorus-containing reactive flame retardant and the zero-dimensional nanoparticles is 100:3.2:0.2;
[0175] The molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.24:1.95:0.24; the phosphorus-containing flame retardant segment uses 2-carboxyethylphenyl hypophosphorous acid and DDP, and the molar ratio of the two is 8:2; the zero-dimensional nanoparticles use nano-silicon dioxide and nano-carbon black.
[0176] (2) mixing conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets, melt blending and extrusion granulation at 269° C. to obtain a core layer polyester material with a melting point of 238° C.; the mass ratio of conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets is 100:8.5:0.2;
[0177] The characteristic viscosity of the conventional melting point polyester of the core layer is 0.67 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 1; and the modified two-dimensional nanosheet is modified attapulgite.
[0178] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 45wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 329°C, the spinning speed is 4160m / min; the drawing temperature is 65°C, and the drawing multiple is 2.47 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0179] Example 13
[0180] The preparation method of the low melting point flame retardant polyester sheath-core fiber in this embodiment includes:
[0181] (1) terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, a phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are copolymerized at 222°C, extruded and granulated to obtain a low-melting-point polyester material with a skin layer having a melting point of 87°C; the mass ratio of the sum of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, the phosphorus-containing reactive flame retardant and the zero-dimensional nanoparticles is 100:9.5:2.8;
[0182] The molar ratio of terephthalic acid, isophthalic acid, ethylene glycol and diethylene glycol is 1:0.48:2.45:0.39; the phosphorus-containing flame retardant segment uses 2-carboxyethylphenyl hypophosphorous acid and DDP, and the molar ratio of the two is 2:8; the zero-dimensional nanoparticles use nano carbon black.
[0183] (2) mixing conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets, melt blending and extrusion granulation at 289° C. to obtain a core layer polyester material with a melting point of 263° C.; the mass ratio of conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets is 100:18.5:2.8;
[0184] The characteristic viscosity of the conventional melting point polyester of the core layer is 0.84 dL / g; the phosphorus-containing non-reactive flame retardant is non-reactive flame retardant 3; and the modified two-dimensional nanosheet is modified attapulgite.
[0185] (3) The core layer polyester material is used as the inner core and the skin layer polyester material is used as the outer skin, and low melting point flame retardant polyester core-skin fiber is obtained by melt spinning, wherein the skin layer accounts for 48wt% of the total mass of the low melting point flame retardant polyester core-skin fiber; wherein the spinning temperature is 288°C, the spinning speed is 3100m / min; the drawing temperature is 79°C, and the drawing multiple is 3.15 times. The performance of the low melting point flame retardant polyester core-skin fiber is tested, and the test results are shown in Table 1.
[0186] Comparative Example 1
[0187] The method of Example 1 was followed, except that "the spinning temperature was 307° C." was replaced by "370° C.". The test results are shown in Table 1.
[0188] Comparative Example 2
[0189] The method of Example 1 was followed, except that "the spinning speed is 3900 m / min" was replaced by "4600 m / min". The test results are shown in Table 1.
[0190] Comparative Example 3
[0191] The method of Example 1 was followed, except that "the stretching temperature was 72° C." was replaced by "115° C.". The test results are shown in Table 1.
[0192] Comparative Example 4
[0193] The method of Example 1 is followed, except that "the drafting ratio is 2.8 times" is replaced by "4.0 times". The test results are shown in Table 1.
[0194] Comparative Example 5
[0195] The method of Example 1 is used, except that the modified two-dimensional nanosheets are not subjected to surface modification treatment with melamine amide, that is, the original two-dimensional nanosheets are used. The test results are shown in Table 1.
[0196] Comparative Example 6
[0197] The method of Example 1 was followed, except that "copolymerization of terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol, phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles at 240° C." was replaced by "280° C." The test results are shown in Table 1.
[0198] Comparative Example 7
[0199] The method of Example 1 was followed, except that "the conventional melting point polyester, phosphorus-containing non-reactive flame retardant and high aspect ratio two-dimensional nanosheets were melt blended at 290° C." was replaced with "350° C." The test results are shown in Table 1.
[0200] Comparative Example 8
[0201] The method is the same as in Example 1, except that the zero-dimensional nanoparticle nanosilica is absent. The test results are shown in Table 1.
[0202] Comparative Example 9
[0203] The method is the same as in Example 1, except that the modified two-dimensional nanosheet is missing. The test results are shown in Table 1.
[0204] Comparative Example 10
[0205] The method is the same as in Example 1, except that the phosphorus-containing reactive flame retardant is only 2-carboxyethylphenylphosphite. The test results are shown in Table 1.
[0206] Comparative Example 11
[0207] The method is the same as in Example 1, except that only DDP is used as the phosphorus-containing reactive flame retardant. The test results are shown in Table 1.
[0208] Comparative Example 12
[0209] The method is the same as in Example 1, except that the phosphorus-containing non-reactive flame retardant is absent. The test results are shown in Table 1.
[0210] Table 1 Performance characterization results of low melting point flame retardant polyester sheath-core fibers prepared in Examples 1-13 and Comparative Examples 1-12
[0211]
[0212]
[0213] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0214] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A low melting point flame retardant polyester sheath-core fiber, characterized in that: Includes cortex and core layer; The cortex comprises a low-melting polyester and zero-dimensional nanoparticles dispersed in the low-melting polyester, the molecular structure of the low-melting polyester comprises a polyester segment and a phosphorus-containing flame-retardant segment, and the phosphorus-containing flame-retardant segment is derived from 2-carboxyethylphenylphosphite and [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid; The core layer includes conventional melting point polyester, phosphorus-containing non-reactive flame retardant dispersed in the conventional melting point polyester and modified two-dimensional nanosheets, wherein the phosphorus-containing non-reactive flame retardant includes any one or more combinations of phosphate flame retardants and phosphaphenanthrene flame retardants.
2. The low melting point flame retardant polyester sheath-core fiber according to claim 1, characterized in that: The skin layer includes the following components calculated by weight: 100 parts of low melting point polyester and 0.1 to 3 parts of zero-dimensional nanoparticles; and / or, the mass ratio of the low melting point polyester to the zero-dimensional nanoparticles in the skin layer is 100:(0.5-2), preferably 100:(1-1.5); And / or, the skin layer accounts for 10-50wt% of the total mass of the low-melting point flame-retardant polyester sheath-core fiber.
3. The low melting point flame retardant polyester sheath-core fiber according to claim 1, characterized in that: The intrinsic viscosity of the low melting point polyester is 0.54 to 0.68 dL / g, preferably 0.58 to 0.66 dL / g, and particularly preferably 0.60 to 0.64 dL / g; And / or, the melting point of the low-melting-point polyester is 85° C. to 145° C.; And / or, the polyester segment includes a terephthalic acid segment, an isophthalic acid segment, an ethylene glycol segment and a diethylene glycol segment; Preferably, the molar ratio of the terephthalic acid segment, the isophthalic acid segment, the ethylene glycol segment and the diethylene glycol segment is 1:(0.2-0.5):(1.8-2.5):(0.2-0.4); And / or, the mass ratio of the low melting point polyester to the phosphorus-containing flame retardant segment in the low melting point polyester is 100:(3-10), preferably 100:(5-7); And / or, the zero-dimensional nanoparticles include any one or more combinations of nano-silicon dioxide and nano-carbon black.
4. The low melting point flame retardant polyester sheath-core fiber according to claim 1, characterized in that: The core layer comprises the following components calculated by weight: 100 parts of conventional melting point polyester, 8-20 parts of phosphorus-containing non-reactive flame retardant and 0.1-3 parts of modified two-dimensional nanosheets; and / or, the mass ratio of the conventional melting point polyester to the phosphorus-containing non-reactive flame retardant in the core layer is 100:(10-18), preferably 100:(13-16); And / or, the mass ratio of the conventional melting point polyester to the modified two-dimensional nanosheets in the core layer is 100:(0.5-2), preferably 100:(1-1.5).
5. The low melting point flame retardant polyester sheath-core fiber according to claim 1, characterized in that: The molecular structure of the conventional melting point polyester includes terephthalic acid segments and ethylene glycol segments; and / or, the conventional melting point polyester comprises polyethylene terephthalate; and / or, the melting point of the conventional melting point polyester is 235° C. to 265° C.; and / or, the intrinsic viscosity of the conventional melting point polyester is 0.65 to 0.85 dL / g, preferably 0.68 to 0.80 dL / g, and particularly preferably 0.70 to 0.75 dL / g; And / or, the phosphate flame retardant includes a compound having a structure represented by formula (I) or formula (II): And / or, the phosphaphenanthrene flame retardant includes a compound having a structure shown in formula (III): And / or, the modified two-dimensional nanosheets are obtained by surface-modifying the two-dimensional nanosheets with melamine amide; preferably, the two-dimensional nanosheets include any one or more combinations of nano-sized montmorillonite, attapulgite, illite, and sepiolite.
6. The low melting point flame retardant polyester sheath-core fiber according to claim 1, characterized in that: The low-melting point flame-retardant polyester sheath-core fiber has a tensile strength of 3.7 to 5.4 cN / dtex, an elongation at break of 12% to 23%, and a limiting oxygen index of 34 to 46%.
7. The method for preparing the low melting point flame retardant polyester sheath-core fiber according to any one of claims 1 to 6, characterized in that: include: The low melting point polyester monomer, phosphorus-containing reactive flame retardant and zero-dimensional nanoparticles are mixed and copolymerized, and then extruded and granulated to obtain a skin layer polyester material; The conventional melting point polyester, phosphorus-containing non-reactive flame retardant and modified two-dimensional nanosheets are mixed and melted, extruded and granulated to obtain a core layer polyester material; Furthermore, the sheath layer polyester material and the core layer polyester material are subjected to melt spinning to obtain low melting point flame retardant polyester sheath-core fiber.
8. The preparation method according to claim 7, characterized in that: The low melting point polyester monomers include terephthalic acid, isophthalic acid, ethylene glycol, diethylene glycol and a phosphorus-containing flame retardant monomer; wherein the phosphorus-containing flame retardant monomer includes 2-carboxyethylphenylphosphite and [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid (DDP); preferably, the molar ratio of 2-carboxyethylphenylphosphite to [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid in the phosphorus-containing flame retardant monomer is (2-8):(8-2), and particularly preferably (4-6):(6-4); And / or, the process conditions adopted in the melt spinning treatment include: the spinning temperature is 285℃~330℃, the spinning speed is 3000m / min~4200m / min; the stretching temperature is 65℃~80℃, and the stretching ratio is 2.4~3.2 times; preferably, the spinning temperature is 300℃~315℃, the spinning speed is 3800m / min~4000m / min; the stretching temperature is 70℃~75℃, and the stretching ratio is 2.7~2.9 times.
9. The preparation method according to claim 7, characterized in that: Also includes: The two-dimensional nanosheet is subjected to ion replacement treatment to obtain a two-dimensional nanosheet having sodium ions; The two-dimensional nanosheets having sodium ions are mixed with melamine amide and stirred fully, and then phosphoric acid is added and ultrasonically stirred to react to obtain the modified two-dimensional nanosheets.
10. Use of the low melting point flame retardant polyester sheath-core fiber according to any one of claims 1 to 6 in the fields of automobile industry, rail transportation, architectural decoration, medical care or home textiles.
Citation Information
Patent Citations
Flame-retarding low-melting-point polyester fiber and preparation method thereof
CN106811830A
Hydrophilic-lipophilic medical sheath-core type fiber non-woven fabric
CN108950864A
Flame-retardant low-melting-point polyester fibers and preparation method thereof
CN111088555A
Flame-retardant low-melting-point polyester fiber and preparation method thereof
CN113445154A
Flame-retardant low-melting-point polyester fiber and preparation method thereof
CN114574995A
Cited By
Special fiber composite material with ultrahigh mechanical property and preparation method thereof
CN121108692A